Radio, the Genome, and Greg Bear's Biological Fiction. - Dougherty, Stephen (Science Fiction Studies, 2017)
This essay explores the human genome as a form of media via Greg Bear's biological fiction. The genome is a network and a database; it is a product of biopower in the age of digital computers. I argue it is also a rich fantasy object, a conceptual and theoretical staging ground for thinking about the nature of technical media, the human, and the posthuman.